Perbedaan Daya Antijamur pada Basis Gigi Tiruan Resin Akrilik Kuring Dingin Dengan Penambahan Ekstrak Etanol Kulit Batang Rambutan (Nephelium Lappaceum L.) dan Tanpa Penambahan Ekstrak Etanol Kulit Batang Rambutan (Nephelium Lappaceum L.) pada Polimer Metakrilat Terhadap Pertumbuhan Candida Albicans - Yusoh, Sakeenah, drg. Noor Hafida Widyastuti, Sp.KG, drg. Nanang Krisnawan (2015)
Removable denture usually consisted of artificial teeth elements attached on acrylic resin base. Prosthesis application in long term leaned to oral tissues alteration, one of them known as denture stomatitis. Denture disinfection was an important procedure to apply, sanitizing the prosthesis to avoid it from C.albicans, common yeast that caused denture stomatitis. The purpose of this study was to find out the difference between antifungal effect on cold curing acrylic resin denture base with rambutan skin stem ethanol extract addition and the one without rambutan skin stem ethanol extract addition on methacrylate polymer against C.albicans growth. Study sample consisted of 32 square plates acrylic resin (10x10x1 mm), divided into 2 groups, a group with additional ethanol extract of rambutan stem skin and another group without it on methacrylate polymer. These plates were submerged into 10 ml of C.albicans suspension, each sample were mixed on vortex mixer and diluted into dilution series 10-3. The dilution then spread on Sabouraud agar plate. The amount of appeared C.albicans was counted and the data were put in a formula to find out the fungus number. Obtained data were analyzed using Shapirowilk test, Levene's test, and Independent t test on 95% significance level (α = 0,05). The study showed significant p value p=0.022 (p<0.05) means that there was differences of antifungal effect of cold curing acrylic resin denture base with additional ethanol extract of rambutan (nephelium lappaceum l.) stem skin and the one without it on methacrylate polymer against C. albicans growth